Why does advantageous inequity promote prosocial behavior? The roles of justice sensitivity and guilt - Jinyao Zhu; Cuizhen Liu (Acta Psychologica)
Previous research has shown that advantageous inequity promotes prosocial behavior. However, little is known about the underlying mechanisms that contribute to this phenomenon. This study investigated the potential roles of justice sensitivity and emotion as key mechanisms in this process. Using a justice sensitivity scale, which includes four subscales (victim sensitivity, observer sensitivity, beneficiary sensitivity and perpetrator sensitivity), university students were recruited as participants and divided into two groups: high justice sensitivity (N = 44) and low justice sensitivity (N = 51). Results showed that individuals with high justice sensitivity were more inclined to increase their partner's payoff at their own cost under advantageous inequity, compared to those with low justice sensitivity. Emotionally, participants primarily experienced guilt and empathy, rather than anger, shame, or delight when facing advantageous inequity. Moderated mediation analyses revealed that participants with high justice sensitivity displayed a greater tendency to experience guilt (but not empathy) under advantageous inequity, which subsequently led to increased prosocial behavior, in comparison to those with low justice sensitivity. These findings highlight the roles of justice sensitivity and guilt in shaping prosocial behavior within advantageous inequity contexts.